Stock management: case of study applied to furniture businesses in Carmo do Cajuru, MG (Research, Society and Development, 2018)
The goal of this paper was to demonstrate the benefits of using the ABC curve in the management of raw material stock in small furniture companies in Carmo do Cajuru, MG. A descriptive research with a qualitative approach was carried out by two case studies. The data were collected by interviews and a questionnaire applied to the managers of the companies, besides the unsystematic observation. Thus, a comparison was established between the theory studied and the practice of inventory management of companies, one of which used the ABC curve and the other did not use it. The result showed that the use of the ABC curve offers several benefits to the inventory management of small furniture companies, among them the increase of the efficiency of its management, contributing to the optimization of the physical space of storage and reduction of the financial investment in raw materials.